Experimental evaluation of an unmodified diesel engine using biodiesel with fuel additive - Masjuki, Haji Hassan; Kalam, M.A.; Syazly, M.; Mahlia, T.M.I.; Rahman, A.H.; Redzuan, M.; Varman, M.; Saidur, Rahman; Yau, Y.H. (2006)
This paper presents experimental results carried out to evaluate the brake power, specific fuel consumption (SFC) and exhaust gas emissions when running on an unmodified diesel engine with fuel additive blended biodiesel. The multi-functional fuel additive was added (in mass basis) with B20 (20 biodiesel and 80 ordinary diesel fuel) in a special manner to increase engine brake power. For comparisons three fuels were tested in this investigation which are (1) B20X where X is the percentage of fuel additive, (2) B20 and (3) BO (0 biodiesel and 100 ordinary diesel fuel). The stationary engine test bed used consists of a multi-cylinder diesel engine, eddy current dynamometer with computer control data acquisition system and exhaust emissions analyzer. The exhaust emissions such as CO, HC, and NOx were measured using exhaust gas analyzer. It is found that B20X produces higher performance (brake power) with reduction in exhaust emissions and fuel consumption as compared to B20 and BO fuels. Fuel "B20X" could be a 'breakthrough' and the real solution as an alternative fuel for existing unmodified diesel engine. Detail results including B20X fuel's physicochemical properties are presented with discussions.